Holistic Comprehensive Approach to Conquer Ankylosing Spondylosis with Homoeopathic Modality (Homoeopathy for All, 2026)
Ankylosing spondylosis (AS) is a chronic inflammatory rheumatic dis order primarily affecting the axial skeleton, causing progressive stiff ness, postural deformity, and restrict ed mobility. It is closely associated with HLA-B27 positivity, signifying a strong autoimmune component. Conventional management relies on NSAIDs, corticosteroids, and biolog ics, which may provide temporary relief but often lead to adverse effects such as gastric irritation and steroid dependency.
Keywords: HLA-B27; Ankylosing spondylosis (AS); Spondylitis; immune system dysfunction